Corticosteroids added to antibiotic therapy aid pain resolution in adults with sore throat, particularly severe or exudative sore throat. Issue 1 (22nd February 2010) - McIsaac, Warren
Abstract : Commentary on: Hayward G Thompson M Heneghan C . Corticosteroids for pain relief in sore throat: systematic review and meta-analysis . BMJ 2009 ;339 :b2976 .